Mother India : A Political Biography of Indira Gandhi - Pranay Gupte (India Penguin Books India, 2011)
Mother India is the fascinating story of independent India's most complex GUPTE political figure: Indira Gandhi, the enigmatic and solitary daughter of the country's first prime minister, who rose to become prime minister herself.
The first major biography of Indira Gandhi covers the breadth and scope of 20th-century India and the woman who left her indelible mark on that troubled country. Both widely supported and bitterly opposed, she was eventually removed from office, only to make a stunning comeback.
Include Illustrations, Bibliography and Index.
A Political Biography of Indira Gandhi.
Keywords: India -- Prime ministers -- Politics and government